首陽山의 位置에 관한 論難과 그 詩的 形象化 - 이현정 (동양한문학연구, 41(41), 2015)
본고는 首陽山의 위치를 둘러싼 논란과 그 근원을 분석하여 그것이 한시에서 어떻게 형상화 되고 있는지를 밝히는 것을 목적으로 한다. 수양산의 위치에 대한 논의는 총 6곳(黃海道 海州를 포함하면 7곳)에서 이루어졌지만 백이가 은거한 곳이 어디인지는 정확하지 않다. 조선에서는 그 틈을 비집고 들어가 황해도 해주가 백이가 은거한 곳이라고 주장한 경우가 있어 주목된다. 小中華를 자처하며 유가의 정통을 계승하고자 했던 조선의 사대부들이 不事二君의 節義를 상징하는 백이와 숙제를 숭배한 것은 어쩌면 당연한 일이었다. 또 백이가 은거한 수양산이 조선에 있다는 주장은 중국의 문헌을 근거로 했기 때문에 허황된 것이 아니었다. 후기에 들어서면 이에 대한 반성적 논의가 일어나기도 하지만 황해도 해주의 수양산이 백이가 은거한 곳이라 믿는 문인들은 여전히 존재하였다. 이러한 인식을 바탕으로 한시에서 수양산이 언급된 양상을 살펴본 결과, 절의로 대표되는 백이와 그가 은거한 공간인 수양산이 우리나라, 조선에서 어떠한 의미를 지니는지를 짐작할 수 있었다. This paper is aiming at controversy about surrounding the position of Mt.Soo-yang and examining the aspect of configuration on the Korean Chinese poem. Bo-yi(伯夷) and Shu-qi(叔齊) were said to have been the retire to hermitage in the Mt.Soo-Yang was a total of seven locations in China and Korea. The location of the Mt.Soo-Yang had been focused on Loyang and Puban In China and Hwanghaedo Haeju in Korea. In Korea, disscussion about the location of Mt.Soo-yang begin in earnest during the Joseon Dynasty, and The king conferred the shrinea of Bo-yi and Shu-qi posthumous epithet. In China, focussed on where is the Mt.Soo-Yang. In Korea, they put emphasis on the reason Mt.Soo-Yang must be in Haeju. Bo-yi who Against the ‘Righteousness(不意)’ and died of starvation was clearly revealed the value of the ‘Loyalty(忠)’, and Mt.Soo-Yang Bo-yi died of starvation was same. The Joseon Dynasty was country faithfully followed the value of the Boyi under the banner of Neo-Confucianism. It will be discussed later, they argued that Mt.Soo-Yang must be in Haeju, I can possibly agree with their effort. According to the recognition of Mt.Soo-yang, it is generally divided three Patterns. Boyi is represented by Fidelity and Mt.Soo-yang can ba seen in Joseon Dinasty. KCI Citation Count: 1